Examining The Influencing Factors Of R&D Engineers Creativity In Original Design Manufacturing Sector - Chang, Yen Ping (2014)
The purpose of this study is to examine the direct effect of the perception of organizational learning variables, the perception of organizational factors and knowledge management efficiency with Research and Development (R&D) engineer’s creativity; and investigate whether knowledge management have moderating effect in the above relationship. Organizational learning variable comprises of four sub-elements which is the managerial commitment, system perspective, openness & experimentation, knowledge transfer& integration. Meanwhile organizational factor consist five sub-elements of organization support, organization integration, information & communication, organization resources, corporate culture.